Kesaksian Satu Orang Wanita pada Masalah yang Hanya Diketahui oleh Kalangan Wanita Menurut Empat Mazhab: Testimony of a Woman on Issues Known Exclusively to Women According to the Four Jurisprudential Schools - Jujuri Perdamaian Dunia; Patahuddin, Askar; Nuraeni Novira; Sasi Muliana (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to know and understand the Existence of Hijab as an Effort to Protect Muslim Women from the Maqāṣid al-Syarī'ah Perspective. The purpose of this study is also to find out how the urgency of the hijab is in Islamic law and how the existence of the hijab provides protection for Muslim women, and to find out how the elements of maqāṣid al-syarī'ah in the hijab of Muslim women. The method used in this study to get answers to the problems above is using library research with a qualitative descriptive type of research, using normative and philosophical approaches. The results of the study found that the hijab has an important role in Islam. Some of the urgency of the hijab, namely the hijab as a form of obedience to Allah swt. and His Messenger, the hijab can reduce various kinds of slander, and more importantly the hijab makes women more respectable and protected. Hijab protects women by covering their nakedness and curves and the beauty they have so that they do not cause slander and do not invite lust or dirty thoughts for those who look at them. The hijab order was revealed by Allah swt. certainly has benefit both in this world and in the hereafter. By wearing the hijab, the religion, soul, intellect, property and lineage of a Muslim woman will be maintained.